(untitled) (Conference Zone, 2022)
In order to organize education on a correct, scientific basis, it is necessary to know the specific psychological laws of this process, its mechanisms, the laws of development at different ages, as well as effective ways to structure the process of active, independent and creative thinking. In this regard, information and communication technologies play an important role in the educational process. This article discusses the development of psychological characteristics of students in the education system, the ongoing reforms in the country, the problem of long-term retention of knowledge in the memory of students, as well as the role and importance of video lessons in solving this problem. In particular, the positive opportunities that students achieve when using video lessons in the educational process are revealed.